RENOVASI TAMAN BUDAYA SUMATERA UTARA - Dr. Darwin Sinabariba, ST, MM (Jurnal Sains dan Teknologi ISTP, 2021)
In accordance with one of the nature of art, the creative, the art can be used by humans to create new creations, follow the values that flourish in society. It is notnecessary to create a place and time limitation, but to create something that can be known and have an impact on the community, there are factors that must be considered, such as the venue and rehearsal space. Medan should have a representative and iconic place to the value of art. Representative and iconic to the general public’s point of view so easily recognized and emerging interest to try doing activities in it. From there will come the desire to try to watch, until finally trying to learn. The figures of art and artist to create the maximum to be able to provide a dish of performing arts to the community, to get involved in giving direction or depth for interested communities. Taman Budaya Sumatera Utara was the most actively used by the artists of Medan. Own function as a place of training and coaching of art and culture. It’s necessary to rejuvenate the Taman Budaya Sumatera Utara that is functionally and physically able to run properly and function more optimally.